Tracheal replacement. Issue 2 (15th February 2018) - Etienne, Harry; Fabre, Dominique; Gomez Caro, Abel; Kolb, Frederic; Mussot, Sacha; Mercier, Olaf; Mitilian, Delphine; Stephan, Francois; Fadel, Elie; Dartevelle, Philippe
Tracheal reconstruction is one of the greatest challenges in thoracic surgery when direct end-to-end anastomosis is impossible or after this procedure has failed. The main indications for tracheal reconstruction include malignant tumours (squamous cell carcinoma, adenoid cystic carcinoma), tracheoesophageal fistula, trauma, unsuccessful surgical results for benign diseases and congenital stenosis. Tracheal substitutes can be classified into five types: 1) synthetic prosthesis; 2) allografts; 3) tracheal transplantation; 4) tissue engineering; and 5) autologous tissue composite. The ideal tracheal substitute is still unclear, but some techniques have shown promising clinical results. This article reviews the advantages and limitations of each technique used over the past few decades in clinical practice. The main limitation seems to be the capacity for tracheal tissue regeneration. The physiopathology behind this has yet to be fully understood. Research on stem cells sparked much interest and was thought to be a revolutionary technique; however, the poor long-term results of this approach highlight that there is a long way to go in this research field. Currently, an autologous tissue composite, with or without a tracheal allograft, is the only long-term working solution for every aetiology, despite its technical complexity and setbacks. Autologous composite tissue and tracheal transplantation have given promising results in tracheal replacement http://ow.ly/PLrq30hNUeP